An AAST-MITC analysis of pancreatic trauma: Staple or sew? Resect or drain?. Issue 3 (September 2018) - Byrge, Nickolas; Heilbrun, Marta; Winkler, Nicole; Sommers, Daniel; Evans, Heather; Cattin, Lindsay M.; Scalea, Tom; Stein, Deborah M.; Neideen, Todd; Walsh, Pamela; Sims, Carrie A.; Brahmbhatt, Tejal S.; et al.
Abstract : INTRODUCTION: Pancreatic trauma results in high morbidity and mortality, in part caused by the delay in diagnosis and subsequent organ dysfunction. Optimal operative management strategies remain unclear. We therefore sought to determine CT accuracy in diagnosing pancreatic injury and the morbidity and mortality associated with varying operative strategies. METHODS: We created a multicenter, pancreatic trauma registry from 18 Level 1 and 2 trauma centers. Adult, blunt or penetrating injured patients from 2005 to 2012 were analyzed. Sensitivity and specificity of CT scan identification of main pancreatic duct injury was calculated against operative findings. Independent predictors for mortality, adult respiratory distress syndrome (ARDS), and pancreatic fistula and/or pseudocyst were identified through multivariate regression analysis. The association between outcomes and operative management was measured. RESULTS: We identified 704 pancreatic injury patients of whom 584 (83%) underwent a pancreas-related procedure. CT grade modestly correlated with OR grade (r 2 0.39) missing 10 ductal injuries (9 grade III, 1 grade IV) providing 78.7% sensitivity and 61.6% specificity. Independent predictors of mortality were age, Injury Severity Score (ISS), lactate, and number of packed red blood cells transfused. Independent predictors of ARDS were ISS, Glasgow Coma Scale score, and pancreatic fistula (OR 5.2, 2.6–10.1). Among grade III injuries (n = 158, 22.4%), the risk of pancreatic fistula/pseudocyst was reduced when the end of the pancreas was stapled (OR 0.21, 95% CI 0.05–0.9) compared with sewn and was not affected by duct stitch placement. Drainage alone in grades IV (n = 25) and V (n = 24) injuries carried increased risk of pancreatic fistula/pseudocyst (OR 8.3, 95% CI 2.2–32.9). CONCLUSION: CT is insufficiently sensitive to reliably identify pancreatic duct injury. Patients with grade III injuries should have their resection site stapled instead of sewn and a duct stitch is unnecessary. Further study is needed to determine if drainage alone should be employed in grades IV and V injuries. LEVEL OF EVIDENCE: Epidemiologic/Diagnostic study, level III.